Pneumomediastinum as a manifestation of a bronchial carcinoid tumour: a very rare association of two uncommon diseases (Emergency Care Journal, 2024)
A 29-year-old man presented to the emergency department with haemoptysis and thoracic pain. His vital signs and blood tests were normal, except for increased C-reactive protein levels. Fibrolaryngoscopy and esophagogastroduodenoscopy results were negative. Computed Tomography of the chest revealed abundant pneumomediastinum, air dissection along the peribronchovascular sheaths of the left lower lobe and a vegetating lesion completely occluding the distal extremity of the left main bronchus. After complete bronchoscopic excision of the lesion, histological examination revealed a carcinoid tumour not otherwise specified. After hospital discharge, 18F-fluorodeoxyglucose and 68Ga-DOTANOC positron emission tomographies ruled out distant metastases. A sleeve resection of approximately 20 mm of the distal extremity of the left main bronchus and a circumferential anastomosis between the left main bronchus and ipsilateral lobar bronchi were performed. Several bronchoscopic follow-ups did not show anastomotic dehiscence or tumour relapse.
Keywords: Bronchial carcinoid tumour; pneumomediastinum; Macklin effect; Computed Tomography; bronchoscopy; thoracic surgery; thorax; chest